GPR15 in colon cancer development and anti-tumor immune responses - Namkoong, Hong; Lee, Bomi; Swaminathan, Gayathri; Koh, Seong-Joon; Rogalla, Stephan; Paraskevopoulou, Maria D.; Tang, Jay; Mikhail, David; Becker, Laren S.; Habtezion, Aida (Frontiers in Oncology, 2023)
Abstract The chemoattractant receptor, G protein-coupled receptor 15 (GPR15) in response to its ligand, C10orf99/GPR15L, promotes colon homing of T cells in health and colitis. GPR15 function in colon cancer is largely unexplored, motivating our current studies using human colorectal cancer (CRC) tissues and murine colon cancer models. Our analysis of human CRC tissue revealed a significant reduction in GPR15+ immune cell frequencies in tumors compared to ‘tumor-free’ surgical margins. Furthermore, our analysis of data obtained from The Cancer Genome Atlas (TCGA) database indicated that lower GPR15 expression is associated with poor survival in human colon cancer. In the AOM/DSS colitis-associated murine colon cancer model, we observed increased colon polyps and lower survival in Gpr15-deficient (KO) compared to Gpr15-sufficient (Het) mice. Analysis of immune cell infiltrates in the colon polyps showed significantly decreased CD8+ T cells and increased IL-17+ CD4+ and IL-17+ CD8+ T cells in Gpr15-KO compared to Gpr15-Het mice. GPR15 deficiency thus alters the immune environment in colon polyps to mitigate T cell-mediated anti-tumor responses resulting in severe disease. Consistent with a protective role of GPR15, administration of GPR15L to established tumors in the MC38-CRC model dramatically reduced tumor burden. Our findings highlight an important role of the GPR15-GPR15L axis in promoting a tumor-suppressive immune microenvironment and unveils a novel, colon-specific therapeutic target for CRC.